Transition to adult diabetes care in Germany—High risk for acute complications and declining metabolic control during the transition phase. Issue 6 (10th May 2018) - Kapellen, TM; Müther, S; Schwandt, A; Grulich‐Henn, J; Schenk, B; Schwab, KO; Marg, W; Holl, RW; ,
Abstract : Objective: There is evidence that transition from pediatric to adult health care is frequently associated with deterioration of health in youths with type 1 diabetes (T1D). The aim of this study was to compare metabolic control, acute complications and microvascular complications in adolescents and young adults before and after transfer to an adult treatment center with respect to the time between first visit in the adult center and last visit in pediatric treatment. Methods: All data were collected during routine care and retrieved from the German/Austrian DPV database. We analyzed data as of March 2017. Results: We found 1283 young adults with available data of the last pediatric treatment year and the first year after transition to adult care. HbA1c increased significantly from 8.95% (74 mmol/mol) before to 9.20% (77 mmol/mol) in the first year after transition. Frequency of DKA with hospitalization (0.10‐0.191 per annum, P < .0001) and severe hypoglycemia (0.23‐0.46 per annum, P = .013) doubled during transition. Microvascular complications increased dramatically depending on the time between first visit in adult treatment and last visit in pediatric care. We could not find a significant correlation of this rise of microvascular complications to the duration of transition (short or long). Conclusion: This phase of life bears a high risk for detrimental outcome in young adults with T1D. Structured transition programs with case management are therefore needed to improve the transition process and outcomes.